(untitled) (Biological Sciences - PJSIR, 2000)
An improved synthesis of some newfully substituted-5,6-diphenyl-l,2,4-triazines starting from 4H-2-cyanomethyl/aryl-5,6- diphenyl-l,3,4-oxadiazines (3a-d) has been reported. The structures were determined through elemental analysis and spectral data.The mass spectraof thesynthesizedcompounds werealso studied.Someof thesecompoundsexhibited significant antimi- crobial activity.